PHYSICOCHEMICAL CHARACTERISTICS OF LLAMA JERKY - Mamani-Linares, Willy (2011)
The aim of this study was to determine the physicochemical characteristics of llama jerky. Twenty pieces of jerky, each 450 to 500 g were purchased from various markets and local butchers in the Oruro city, Bolivia. It was determined moisture, fat, protein, ash, cholesterol, minerals, fatty acid profile, total and soluble collagen, Thiobarbituric Acid Reactive Substances, colour, pH, water activity, water holding capacity and Warner- Bratzler shear-force. Llama jerky was characterized by a high protein content, low moisture and water activity, while mineral composition, polyunsaturated to saturated fatty acids ratio and conjugated linoleic acid content were comparable to those found for alpaca and beef jerky. Llama jerky showed a good n-6/n-3 (3.7) ratio and high levels of desirable fatty acids (70.27%). Technological quality parameters of llama jerky were in the range reported for more conventional jerky type.